Rapid detection of foodborne bacterial pathogens using visual high‐throughput microfluidic chip. Issue 5 (31st January 2020) - Jin, Zengjun; Ding, Guotao; Li, Guiying; Yang, Guoxing; Han, Yonghong; Hao, Ning; Deng, Jian; Zhang, Yan; Zhang, Wei; Li, Weihao
Abstract: BACKGROUND: Foodborne diseases are a major global public health concern. It is urgent to monitor foodborne pathogens from contaminated foods based on multi‐target detection. RESULTS: In this work, a self‐priming compartmentalization (SPC) microdevice made of poly(methyl methacrylate) (PMMA) was developed and integrated into a loop‐mediated isothermal amplification (LAMP) system for performing high‐throughput visual detection. The microfluidic chip is a self‐filling microwell array which can introduce reaction solution only through an access hole in a vacuum pumping system. The independent and closed wells can avoid cross‐contamination and ensure the accuracy of the results. The approach was able to perform the simultaneous identification of six foodborne pathogens ( Salmonella typhimurium, Bacillus cereus, Staphylococcus aureus, Yersinia enterocolitica, Vibrio parahaemolyticus and Listeria monocytogenes ) within 1 h. The results demonstrated that the method could specifically recognize the six foodborne pathogens. CONCLUSION: The use of a LAMP‐based microdevice can be a faster alternative to conventional methods to detect pathogens in food samples, especially for those foods in which no pathogen is allowed ( S. aureus ), or foods for infant use. The simplicity and portability of the device can provide an alternative platform for foodborne pathogens where food safety needs accurate and timely detection confirmation. © 2020 Society of Chemical Industry